Utilization of Fetal Hemoglobin Parameters in Predicting Clinical Severity of Sickle Cell Disease: Retrospective Study From a Tanzanian Cohort - Haji HM; Urio F; Nkya S; Chamba C; Nasser A; Lyimo M; Ally M; Mawalla W; Jonathan A; Kidenya B; Mutagonda R; Chirande L; et al. (Journal of Blood Medicine)
Hadiya M Haji,1,2 Florence Urio,1,3,4 Siana Nkya,3,4 Clara Chamba,2 Ahlam Nasser,2 Magdalena Lyimo,2,3 Mwashungi Ally,1– 3 William Mawalla,2 Agnes Jonathan,1,3 Benson Kidenya,1,5 Ritah Mutagonda,1,6 Lulu Chirande,1,7 Paschal Ruggajo,1,8 Emmanuela Ambrose,1,3,9 Emmy Metta,1,10 Emmanuel Balandya,1,3 Julie Makani1– 3 1Sickle Pan-African Research Consortium (SPARCO) - Tanzania, Dar es Salaam, Tanzania; 2Department of Haematology and Blood Transfusion, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 3Sickle Cell Program, Department of Hematology and Blood Transfusion, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 4Department of Biochemistry and Molecular Biology, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 5Department of Biochemistry and Molecular Biology, Catholic University of Health and Allied Sciences, Mwanza, Tanzania; 6Department of Clinical Pharmacy and Pharmacology, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 7Department of Paediatrics and Child Health, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 8Medical College, Aga Khan University, Dar es Salaam, Tanzania; 9Department of Pediatrics, Bugando Medical Centre, Mwanza, Tanzania; 10Department of Behavioral Sciences, Muhimbili University of Health and Allied Sciences, Dar es Salaam, TanzaniaCorrespondence: Hadiya M Haji, Department of Hematology and Blood Transfusion, Muhimbili University of Health and Allied Sciences, P.O. Box: 65001, Dar es salaam, Tanzania, Tel +255 777753436, Email hadiyamahadhi20@hotmail.comBackground: Fetal hemoglobin (HbF) is found at a measurable amount in red blood cells (RBCs) called F cells. High fetal hemoglobin (HbF) levels are linked with milder forms of sickle cell disease (SCD). However, some patients with high HbF levels still have severe symptoms. This variability has been associated with HbF per F cell (HbF/F cell) concentration; thus, it is hypothesized that high HbF/F cell (≥ 10 pg) is crucial in determining SCD disease severity rather than the overall HbF and F cell levels. This study assessed the utility of these three HbF parameters as predictors of SCD clinical events in Tanzania.Methods: A retrospective cohort study was conducted at Muhimbili University of Health and Allied Sciences, involving 92 SCD individuals aged ≥ 6 years, not on hydroxyurea, between September 2022 and February 2023. Data was collected from the Sickle Pan-African Research Consortium (SPARCO)-Tanzania registry. HbF/F cell was calculated as: HbF/F cell = (HbF% × MCH pg)/F cell%. STATA version 15 was used to analyze the association between HbF parameters and clinical events measured by ordinal logistic regression. A p-value < 0.05 was considered statistically significant.Results: Of the 92 SCD participants, the median age was 16 (IQR: 10– 21) years, 53 (57.6%) were below 18 years, and males were 48 (52.2%). Eighty-two patients (89.1%) had HbF/F cells below 10pg. Males had significantly higher HbF/F cell levels with a median of 6.4 (IQR: 4.3– 9.5) pg compared to females 5.3 (IQR: 3.5– 6.5) pg (p-value = 0.004). Although, we did not observe a statistically significant association between HbF/F cell with clinical parameters, increased HbF and F cell percentages correlated with reduced odds of multiple blood transfusions by 11% (p-value = 0.016) and 3% (p-value = 0.020), respectively.Conclusion: In this cohort, HbF and F cell levels remain important predictors of disease severity, as higher levels predicted reduced requirement for multiple blood transfusions in SCD patients, while HbF/F cells did not correlate with SCD clinical events.Keywords: sickle cell, F cell, fetal hemoglobin per F cell, clinical parameters, disease severity